Relation of regional myocardial structure and function in hypertrophic cardiomyopathy and amyloidois: a combined two-dimensional speckle tracking and cardiovascular magnetic resonance analysis. (1st August 2018) - Pagourelias, Efstathios D; Mirea, Oana; Vovas, Georgios; Duchenne, Jürgen; Michalski, Blazej; Van Cleemput, Johan; Bogaert, Jan; Vassilikos, Vasilios P; Voigt, Jens-Uwe
Abstract: Aims: We aimed at investigating the relationship between segmental morphology [wall thickness (WT) and WT location (LT: base-mid-apex)], loading conditions and underlying pathological substrate [histology (H), hypertrophy vs. infiltration] with segmental longitudinal (SLS) and circumferential (SCS) strain in a group of patients with hypertrophic cardiomyopathy (HCM) and cardiac amyloidosis (CA). Methods and results: We included 30 patients with biopsy-proven CA (65.4 ± 10.7 years, 66% male, 76.7% AL type) and 50 patients with HCM matched for maximum WT (60 ± 16 years, 80% male). SLS and SCS were assessed with speckle-tracking echocardiography in an 18-segment model of left ventricle, while morphological parameters were measured in short-axis cardiovascular magnetic resonance cine loops which corresponded with echo segments. In total, 1440 segments were evaluated of which 198 (36.7%) in CA and 252 (28%) in HCM had WT >12 mm (maximum WT 18.1 ± 3.7 mm in CA vs. 18.6 ± 4.1 in HCM, P  = 0.59). SLS showed association with WT [beta 0.49, 95% confidence interval (CI) 0.37–0.6; P  < 0.0005], LT and H ( P  < 0.0005 for both), with CA segments demonstrating 5.94% more impaired SLS compared with HCM segments with the same WT and LT. On the other hand, there was no linear association between SCS and WT, with SCS being dependent on LT, H ( P  < 0.0005) and preload ( P  < 0.002). Conclusion: Our study indicates that regional myocardial mechanics are differentially influenced by local morphological parameters. While SLS is dominated by WT, SCS is more determined by LT and H. These findings may have an important role in diagnosis and prognosis of patients with thickened hearts.